Accurate and reproducible reconstruction of coronary arteries and endothelial shear stress calculation using 3D OCT: Comparative study to 3D IVUS and 3D QCA. Issue 2 (June 2015) - Toutouzas, Konstantinos; Chatzizisis, Yiannis S.; Riga, Maria; Giannopoulos, Andreas; Antoniadis, Antonios P.; Tu, Shengxian; Fujino, Yusuke; Mitsouras, Dimitrios; Doulaverakis, Charalampos; Tsampoulatidis, Ioannis; Koutkias, Vassilis G.; Bouki, Konstantina; et al.
Abstract: Background: Geometrically-correct 3D OCT is a new imaging modality with the potential to investigate the association of local hemodynamic microenvironment with OCT-derived high-risk features. We aimed to describe the methodology of 3D OCT and investigate the accuracy, inter- and intra-observer agreement of 3D OCT in reconstructing coronary arteries and calculating ESS, using 3D IVUS and 3D QCA as references. Methods-Results: 35 coronary artery segments derived from 30 patients were reconstructed in 3D space using 3D OCT. 3D OCT was validated against 3D IVUS and 3D QCA. The agreement in artery reconstruction among 3D OCT, 3D IVUS and 3D QCA was assessed in 3-mm-long subsegments using lumen morphometry and ESS parameters. The inter- and intra-observer agreement of 3D OCT, 3D IVUS and 3D QCA were assessed in a representative sample of 61 subsegments (n = 5 arteries). The data processing times for each reconstruction methodology were also calculated. There was a very high agreement between 3D OCT vs. 3D IVUS and 3D OCT vs. 3D QCA in terms of total reconstructed artery length and volume, as well as in terms of segmental morphometric and ESS metrics with mean differences close to zero and narrow limits of agreement (Bland–Altman analysis). 3D OCT exhibited excellent inter- and intra-observer agreement. The analysis time with 3D OCT was significantly lower compared to 3D IVUS. Conclusions: Geometrically-correct 3D OCT is a feasible, accurate and reproducible 3D reconstruction technique that can perform reliable ESS calculations in coronary arteries. Highlights: We present geometrically correct 3D OCT based on fusion of OCT and angiography. 3D OCT can accurately and reproducibly reconstruct coronary arteries and calculate ESS. Combined functional and anatomical plaque assessment may predict high-risk plaque.